A dimeric bicyclic RGD ligand displays enhanced integrin binding affinity and strong biological effects on U-373 MG glioblastoma cells. Issue 39 (26th September 2019) - Sacco, Giovanni; Dal Corso, Alberto; Arosio, Daniela; Belvisi, Laura; Paolillo, Mayra; Pignataro, Luca; Gennari, Cesare
Abstract : A C 2 -symmetric dimeric bicyclic integrin ligand, bearing two RGD motifs, displays enhanced biological effects compared to monovalent RGD analogues. Abstract : A C 2 -symmetric bicyclic peptide bearing two RGD motifs was developed as a dimeric ligand, and it displayed enhanced inhibition of ECM protein binding to purified integrin receptors as compared to monomeric RGD analogues. Moreover, the dimeric bicyclic ligand induced cell detachment and inhibited FAK phosphorylation in U-373 MG glioblastoma cells.